MicroRNA-214 Suppresses Osteogenic Differentiation of Human Periodontal Ligament Stem Cells by Targeting ATF4 - Siqi Yao; Wei Zhao; Qianmin Ou; Lanchen Liang; Xuefeng Lin; Yan Wang (Hindawi Limited, 2017)
Periodontitis is the main cause of adult tooth loss. Stem cell-based tissue engineering has become a promising therapy for periodontitis treatment. To date, human periodontal ligament stem cells (hPDLSCs) have been shown to be a favorable source for tissue engineering, but modulatory mechanisms of hPDLSCs remain unclear. Approximately 60% of mammalian genes are the targets of over 2000 miRNAs in multiple human cell types, and miRNAs are able to influence various biological processes in the human body, including bone formation. In this study, we found that after osteogenic induction, miR-214 was significantly decreased in hPDLSCs; therefore, we examined the effects of miR-214 on osteogenic differentiation. Computational miRNA target prediction analyses and luciferase reporter assays revealed that activating transcription factor 4 (ATF4) is a direct target of miR-214. We prepared cells overexpressing miR-214 and found that miR-214 negatively regulates osteogenic differentiation of hPDLSCs. For the target of miR-214, ATF4 protein expression level was decreased after induction. In conclusion, we found that miR-214-ATF4 axis is a novel pathway for regulating hPDLSC osteogenic differentiation.